Віддалені наслідки хірургічного лікування хворих із диференційованими формами раку щитоподібної залози - Штода, Д. Є.; Міміношвілі, О. І.; Попандопуло, А. Г.; Ярощак, С. В.; Попандопуло, Д. А.; Корчагін, Є. П. (Clinical Endocrinology and Endocrine Surgery, 2009)
Comparative study of long-term results of combined treatment of differentiated tyroid cancer of I-II stage was made. Clinical data, laboratory functional tests, replacement therapy efficiency, recurrency rate were analised.